A cellular model for the investigation of depot-specific human adipocyte biology - Pinnick, K; Hodson, L; Karpe, F; Todorcevic, M; Hilton, C; Christodoulides, C; McNeil, C (Taylor and Francis, 2017)
Upper-body adiposity is associated with increased metabolic disease risk, whilst lower-body adiposity is paradoxically protective. Efforts to understand the underlying mechanisms require appropriate and reproducible in vitro culture models. We have therefore generated immortalised (im) human preadipocyte (PAD) cell lines derived from paired subcutaneous abdominal and gluteal adipose tissue. These cell lines, denoted imAPAD and imGPAD display enhanced proliferation and robust adipogenic capacities. Differentiated imAPAD and imGPAD adipocytes synthesise triglycerides de novo and respond lipolytically to catecholamine-stimulation. Importantly the cells retain their depot-of-origin ‘memory’ as reflected by inherent differences in fatty acid metabolism and expression of depot-specific developmental genes. These features make these cell lines an invaluable tool for the in vitro investigation of depot-specific human adipocyte biology.